An Analysis on the Strategic Communication of Social Media in Indian Governance: A Review: The Impact of Social Media on Governance and Democratic Practices in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper intends to contextualize the changes occurring in governance and democratic practices around the world as a result of rise of the new information and communication technologies (ICTs). The rise of the social media clearly poses interesting opportunities and dilemmas for modern governments as well as political actors outside the formal structures of power. How well these structures and groups adapt and respond to these new challenges may hold significant consequences for their continuing relevance and ability to function in society.The social media includes digital devices, such as computers, e-mail, internet, multimedia, video conference, mobile phone, satellites, GPRS Technology, Remote sensing Technology, etc. These have the potential of providing vast amount of relevant information to Rural Population in times; Social media has been considered a tool that can be used to achieve rural development goals in developing countries. In the same time, the majority of people living in developing countries and especially those in rural areas lack access to Social Media. Even if there have been many attempts to introduce social media, they have in general not been long-lasting. Importance of knowledge for development is well recognized.From e-mailing and e-commerce to e-governance, internet has brought us all at a single platform leaving the constraints of time and space far behind. The social engagement in socio-politico activities and people’s proactive participation in political agenda is also increased through social media and viral usage of networking. However, our communication process is still in its evolution and in turn its effects can be traced on the socio-economic-political life of the ‘Information Society’.